Applications of MIS in building Electronic Relationship with customers: A case-based study - Arshi Naim (Periodica Journal, 2021)
In the recent years Customer Relationship Management (CRM) has made significant step world over for effective aid to serve customers. During last two years pandemic is suffered globally due to novice virus COVID: 19. In this situation Information systems (IS) and E-commerce witnessed not only major growth but also contributed to social and customer benefits. In this paper, one of the important applications of IS, which is Management Information Systems (MIS) is applied for the purpose of achieving CRM electronically. Management Information Systems has strengthened CRM and firms who have enhanced their business through ECommerce are known as E-CRM. This paper reviews and presents the developments in E-CRM through MIS with one of the example from Dairy Corporation ‘Almarai”, working successfully in the region of KSA. The research paper explains the theoretical concepts of MIS and E-CRM and and also show through this example that how the firm achieved major benefits by the applications of MIS and how customer satisfaction was achieved by integrating MIS and E-CRM. The results show the variation and gaps before the application of MIS in E-CRM for the firm and after the applications. The annual report shows drastic growth, innovation and increase in customer satisfaction for the firm after the application of MIS in E-CRM.
Keywords: Customer Relationship Management; MIS; ECommerce; Customer Satisfaction